Regulatory T cell-derived adenosine induces dendritic cell migration through the Epac-Rap1 pathway - Ring, Sabine; Pushkarevskaya, Anna; Schild, Hansjörg; Probst, Hans Christian; Jendrossek, Verena; Wirsdörfer, Florian; Ledent, Catherine; Robson, Simon Christopher; Enk, Alexander; Mahnke, Karsten (The journal of immunology, 2015)
Dendritic cells (DC) are one target for immune suppression by regulatory T cells (Treg), because their interaction results in reduced T cell stimulatory capacity and secretion of inhibitory cytokines in DC. We show that DC in the presence of Treg are more mobile as compared with cocultures with conventional CD4+ T cells and form DC-Treg aggregates within 2 h of culture. The migration of DC was specifically directed toward Treg, as Treg, but not CD4+ T cells, attracted DC in Boyden chambers. Treg deficient for the ectonucleotidase CD39 were unable to attract DC. Likewise, addition of antagonists for A2A adenosine receptors abolished the formation of DC-Treg clusters, indicating a role for adenosine in guiding DC-Treg interactions. Analysis of the signal transduction events in DC after contact to Treg revealed increased levels of cAMP, followed by activation of Epac1 and the GTPase Rap1. Subsequently activated Rap1 localized to the subcortical actin cytoskeleton in DC, providing a means by which directed locomotion of DC toward Treg is facilitated. In aggregate, these data show that Treg degrade ATP to adenosine via CD39, attracting DC by activating Epac1-Rap1-dependent pathways. As a consequence, DC-Treg clusters are formed and DC are rendered less stimulatory. This adenosine-mediated attraction of DC may therefore act as one mechanism by which Treg regulate the induction of immune responses by DC.
Prepublished online 16 March 2015
Gesehen am 25.06.2020